2016
DOI: 10.1093/mnras/stw1382
|View full text |Cite
|
Sign up to set email alerts
|

Swift J174540.7−290015: a new accreting binary in the Galactic Centre

Abstract: We report on the identification of the new Galactic Center (GC) transient Swift J174540.7-290015 as a likely low mass X-ray binary (LMXB) located at only 16 arcsec from Sgr A ⋆ . This transient was detected on 2016 February 6 th during the Swift GC monitoring, and it showed long-term spectral variations compatible with a hard to soft state transition. We observed the field with XMM-Newton on February 26 th for 35 ks, detecting the source in the soft state, characterised by a low level of variability and a soft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 88 publications
4
23
0
Order By: Relevance
“…′ from Sgr A ⋆ (SGR J1745-2900, Swift J174540.7-290015 and the foreground component towards AX J1745.6-2901) show neutral absorption column densities consistent with the value of Sgr A ⋆ (Coti- Zelati et al 2015;Ponti et al 2016a;. This suggests that the neutral absorption towards Sgr A ⋆ has an ISM origin.…”
Section: Discussionmentioning
confidence: 58%
“…′ from Sgr A ⋆ (SGR J1745-2900, Swift J174540.7-290015 and the foreground component towards AX J1745.6-2901) show neutral absorption column densities consistent with the value of Sgr A ⋆ (Coti- Zelati et al 2015;Ponti et al 2016a;. This suggests that the neutral absorption towards Sgr A ⋆ has an ISM origin.…”
Section: Discussionmentioning
confidence: 58%
“…There are two X-ray transients whose LOSs are very close to Sgr A ⋆ . Swift J174540.7-290015 was discovered in 2016 at 16 arcsec from Sgr A ⋆ (Reynolds et al 2016), with N H,abs = 1.7 × 10 23 cm −2 (tbnew model and WAM00 abundances, Ponti et al 2016). SGR J1745-2900 is located at 2.4 arcsec from Sgr A ⋆ (Rea et al 2013), with N H,abs = 1.9 × 10 23 cm −2 (tbabs model and WAM00 abundances, Coti- Zelati et al 2015).…”
Section: Dust Distribution In the Gc Directionmentioning
confidence: 99%
“…It has been observed that thousands of point-like X-ray sources and extended sources are sitting in this region (e.g. Wang, Gotthelf & Lang 2002;Muno et al 2003Muno et al , 2005Muno et al , 2009Degenaar et al 2012Degenaar et al , 2015Ponti et al 2015aPonti et al , 2016, including Sgr A ⋆ which is the super-massive black hole (SMBH) closest to Earth (e.g. Genzel, Eisenhauer & Gillessen 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a Solar mix of abundances, supersolar abundance in the accretion flow of Sgr A* would explain the enhanced emission from argon but not that of iron. This would imply that iron is depleted relative to other metals in the GC region, such as observed in the accretion material of AX J1745.6-2901 (Ponti et al 2016). Figure 5.…”
Section: Comparison Of Gaussian Line Fits To Theoretical Predictionsmentioning
confidence: 98%